Definition and Physical Attributes that Characterise Settings of Malay Royal Towns in Malaysia - Mohmad Shukri, Sharyzee; Hussaini Wahab, Mohammad; Che Amat, Rohayah; Taib, Idris; Zafarullah Mohamad Rozaly, Mohamad (International Journal of Engineering and Technology, 2018)
Malay Royal towns in Malaysia are the finest examples evolution of early Malay towns dating from the 16th century. However the identity and characteristic of Malay Royal towns is still unclear and continuously been threatened from tremendous changes due to rapid industrialisation, economic development and urbanisation. The extensive urbanisation and rapid development occurring in most of historical towns have significantly eroded the identity, sense of place and physical attributes of the Malay Royal Town. Besides monuments and sites, the scope of this research also covers all properties which are of historic and cultural significance. This research employs qualitative approach that encompasses of literature review of scholarly articles and reports, in-depth interview and structured observation. Based on the historical and physical evidences that are still exist, 9 historical town that gazated as Malay Royal town will be selected as a preliminary study and 5 historical towns will be selected as study area namely; Anak Bukit, Kota Bharu, Seri Menanti, Klang and Kuala Terengganu. The findings gathered from this research too is deemed a comprehensive understanding of attributes of the royal Malay town and further may help in strengthening the Malaysia history.Â